2015
DOI: 10.1111/1468-0009.12139
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Capital Explain Community‐Level Differences in Organ Donor Designation?

Abstract: The findings suggest that community-level factors, including social capital, predict more than half the variation in donor designation. Future interventions should target the community as the unit of intervention and should tailor messaging for areas with low social capital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 69 publications
2
25
0
Order By: Relevance
“…Furthermore, living in a rural community, higher neighbourhood income quintile and lower material deprivation quintile were no longer strongly positively associated with donor registration after adjustment for ethnic concentration among all Ontario residents. In another study examining how community-level factors affect rates of registration for organ donation, Ladin and colleagues 25 found that groups with higher levels of racial homogeneity, native-born residents and other social capital variables had higher registration rates. They suggested that minority populations may have higher rates of altruistic behaviour (i.e., organ donor registration) if they feel less isolated and better integrated with their community.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, living in a rural community, higher neighbourhood income quintile and lower material deprivation quintile were no longer strongly positively associated with donor registration after adjustment for ethnic concentration among all Ontario residents. In another study examining how community-level factors affect rates of registration for organ donation, Ladin and colleagues 25 found that groups with higher levels of racial homogeneity, native-born residents and other social capital variables had higher registration rates. They suggested that minority populations may have higher rates of altruistic behaviour (i.e., organ donor registration) if they feel less isolated and better integrated with their community.…”
Section: Discussionmentioning
confidence: 99%
“…Both concepts tap into the constructs of trust, solidarity and cohesionalthough social capital places more emphasis on the value of social networks and the most commonly used measure of collective efficacy incorporates social control over deviant behaviour (Coleman 1988, Sampson et al 1997, Ansari 2013. Co-operation requires social capital, namely, shared norms, trust and reciprocity (Sretzer & Woolcock 2004, Sampson 2006, Ladin et al 2015. Collective efficacy cannot develop and remain effective if social capital is absent (Ansari 2013), and increased levels of social capital may foster collective efficacy and co-operative behaviour (Collins et al 2014, Ladin et al 2015.…”
Section: Social Capital and Collective Efficacymentioning
confidence: 99%
“…Social capital has been shown to mitigate collective action problems of free ridership by reinforcing norms supporting prosocial behavior [26,27]. Social capital can be used to encourage prosocial behavior, and, in the case of the organ supply, could be used to increase donation.…”
Section: Are Public Health Authorities Morally Obligated To Intervene?mentioning
confidence: 99%
“…The United States has long granted living donors priority on waiting lists, which expresses support for the ethical value of reciprocity [29]. A recent study of more than three million registered drivers in Massachusetts found that community-level sociodemographic and social capital variables, as measured by levels of racial segregation and violent crime, explain more than half of the variation in organ donor status in Massachusetts [26]. This study demonstrated that, beyond living in a neighborhood with low social capital, even living on the border of a neighborhood with low social capital was independently associated with lower levels of organ donor designation, even after controlling for residents' own neighborhood characteristics.…”
Section: Are Public Health Authorities Morally Obligated To Intervene?mentioning
confidence: 99%